Integrated analysis identifies P4HA2 as a key regulator of STAT1-mediated colorectal cancer progression and a potential biomarker for precision therapy - Zhang, Qianshi; Zhang, Yinan; Sun, Zhiwei; Wang, Huanle; Dai, Guohang; Meng, Yue; Shi, Shasha; Ren, Shuangyi (Frontiers in Oncology, 2025)
IntroductionP4HA2 is implicated in regulating tumor microenvironment formation and may play roles in inflammation and tumor immunity. However, its mechanistic involvement in colorectal cancer (CRC) remains largely unexplored.MethodsWe analyzed P4HA2 expression in CRC tissues and correlated it with clinicopathological features. Functional assays (CCK8, wound healing, Transwell) were performed to assess proliferation and migration. Proteomic analysis identified downstream targets, with STAT1/PD-L1 pathway validation.ResultsHigh P4HA2 expression correlated with advanced T/M stages and served as an independent poor prognostic factor. Functional experiments confirmed P4HA2's role in promoting CRC proliferation and migration. Mechanistically, P4HA2 bound to and downregulated STAT1, subsequently modulating the STAT1/PD-L1 pathway.DiscussionOur findings reveal P4HA2 promotes CRC progression and suppresses anti-tumor immunity via STAT1/PD-L1 axis regulation. This study uncovers a novel pathogenic mechanism, positioning P4HA2 as a potential therapeutic target in CRC.